Library Networking: Current Problems and Future Prospects: Papers Based on the Symposium 'Networking: Where from Here?', 1st edition - Luquire, Wilson (Routledge, 2020)
In this book, first published in 1983, experts in US national, state, and regional network associations provide stimulating discussions of their experiences, problems, and successes. This volume is based on the symposium, ‘Networking: Where From Here?’.